Fish assemblages of the St. Joseph River Watershed, Indiana: Effects of mainstem dams. Issue 3 (27th December 2020) - Pyron, Mark; Deegan, Daragh J.
Abstract: We tested for effects of two dams on fish assemblages in the St. Joseph River, Indiana. Fishes were collected by boat electrofisher twice annually, at 23 sites from 1998 to 2018. Fish collection data were aggregated into CPUE counts of species per 500 m, and CPUE were pooled across sites above and below the dams. We used multivariate analyses to test for spatial and temporal variation for assemblages above and below dams. Assemblages above and downstream of the dams differed significantly when examined by collection year. The effects (abundances of fish species) of the dams on fish assemblages were different at the South Bend dam from those at the Elkhart dam. Trajectories of temporal change in fish assemblages above and below dams were all gradual and directional. Temporal variation in fish abundance categorised into trophic traits (guilds) differed by location. We suggest that moderate to high stress from anthropogenic impacts on the St. Joseph River appears to result in high assemblage variation above and below dams. The St. Joseph River fish community appears to be unstable, likely from multiple anthropogenic impacts to water quality, habitat degradation and hydrologic alteration. We found that 25 of 33 hydrologic variables in four of five Indicators of Hydrological Alteration groups were significantly altered from 1931 to 2019. However, hydrology variation as potential disturbance events did not visually match observed temporal assemblage variation.